The Influence of Air Pollutants on the Acute Respiratory Diseases in Children in the Urban Area of Guadalajara - HU, Ramirez-Sanchez; AR, Meulenert-Peña; ME, Garcia-Guadalupe; FO, Garcia-Concepción; J, Alcala-Gutierrez; HH, Ulloa-Godínez (IntechOpen, 2011)
None